Impacts of sport consumers' time perspectives and negative moral emotions on moral reasoning strategies toward sport organization's misconduct - Myoung Kyoung Choi; Joon Sung Lee (Korea Institute of Sport Science, 2021)
Purpose Drawing on Socioemotional Selectivity Theory, the present research aims to investigate how sport consumers' moral reasoning strategies and forgiveness intent toward a sport organization's misconduct depending on the consumers' different time perspectives(expansive vs. limited). Methods An experimental study (total n = 129; Baby Boomer generation = 62, generation MZ = 67) was conducted by utilizing a fictitious scenario depicting a sport organization's misconduct. The proposed hypotheses were tested by conducting T-test, correction analysis, and multiple regression analysis using SPSS 21.0. Results There were significant differences in moral reasoning and forgiveness based on different time perspective. Baby Boomer(MZ) group showed higher(lower) levels of moral rationalization, moral decoupling, and intent of forgiveness compared to MZ(Baby Bommer) group, while showing lower(higher) level of moral coupling. A result also revealed that negative moral emotions had moderating effect between a limited time perspective and moral coupling among MZ participants. Conclusion The results of this study indicated that sport consumers' time perspective has a predictive function on moral reasoning strategies. Thus, it is necessary for sport organizations to establish strategies focusing on the consumers' time perspective to effectively respond to an unexpected crisis.